Denmark : 2019 Article IV Consultation. (IMF Staff Country Reports; Country Report ;, 2019)
The solid performance of the economy continues to be supported by domestic demand and labor market pressures are gradually building. The current account surplus is declining amid higher investment. The outlook is for continued growth with risks tilted to the downside. While overall house price growth has started to soften, elevated household debt remains a key source of risk. Banks are sound and profitable.